Ship stability for masters and mates - Barrass, C. B.; Derrett, D. R. (Oxford : Butterworth-Heinemann, 2012)
Understanding ship stability - the ability of a ship to return to an initial state after disturbing forces and moments - is critical for all maritime students and professionals studying for a deck or engineering certificate of competency, or seeking promotion to a higher rank within marine or naval companies or institutions. The seventh edition of this classic text provides a comprehensive introduction to all aspects of ship stability and ship strength, squat, interaction and trim, materials stresses and forces, with numerous worked examples to assist masters, mates and engineering officers with qualifications and professional practice. New coverage includes content on new materials used in ship construction, developing methods of propulsion and the latest research into resistance. Ship Stability for Masters and Mates is required reading for seafarers and students alike and an important resource for naval architecture students, shipboard officers and shore-based staff, including dry-dock personnel, ship-designers, ship surveyors, port authorities, marine consultants and superintendents. Updated throughout to include new shipping industry developments and regulations, with 9 new chapters, the latest ship stability datasheets, and sample exam questionsProvides a comprehensive introduction to all aspects of ship stability and ship strength, squat, interaction and trim, materials stresses and forcesConcepts are supported with numerous worked examples, clear diagrams, graphs and equations to assist with understanding and application of this critical subject.
Part I: Linking Ship Stability and Ship Motions -- Group Weights, Water Draft, Air Draft, and Density -- Transverse Statical Stability -- Effect of Decreasing Free Surface on Stability -- TPC and displacement curves -- Form Coefficients -- Discussion on LCB Position Relative to Amidships -- Quadrature -- Simpson's Rules for Areas and Centroids -- Quadrature -- Simpson's Rules for Moments of Inertia -- Quadrature -- Simpson's Rules for Centers of Pressure on Transverse Bulkheads -- KB, BM, and KM Calculations and Graphics on Metacentric Diagrams -- Final KG Plus 20 Reasons for Rise in KG -- Angle of List Considerations -- Text, Calculations, and Graphics -- Angle of Heel -- Effects of Suspended Weights -- Angle of List Due to Bilging of Side Compartments -- Heel Due to Turning -- Angle of Loll -- Moments of Statical Stability -- Aspects of Trim -- The Main Factors Involved -- Trim Calculations -- Changing Conditions of Loading -- Trim Calculations -- Satisfying Prescribed Requirements for End Drafts -- Large-Angle Stability Considerations -- GZ and KN Cross Curves of Stability -- Effects of Beam and Freeboard on Large Angle Stability -- Dynamical Stability Relating to Statical Stability Curves -- Changes in Statical Stability Relating to Wave Profiles -- Loss of Quasi-Static Stability -- Hydrostatic Curves and Values for Vessels Initially on Even Keel -- Hydrostatic Curves and Values for Vessels Initially Having Trim by the Bow or by the Stern -- Increase in Draft Due to List -- Combined List and Trim -- Calculating Free-Surface Effects of Slack Tanks with Divisional Bulkheads -- Bilging Effects of Stability -- Permeability Effects -- Effects of Side Winds on Ship Stability -- Icing Allowances Plus Effects on Trim and Stability -- The Sectional Area Curve -- FL and PL Curves Plus Type A and Type B Vessels -- Load Lines and Freeboard Marks -- Timber Ship Freeboard Marks -- IMO Grain Rules for Safe Carriage of Grain in Bulk -- True Mean Draft -- Inclining Experiment (Stability Test) Plus Fluctuations in a Ship's Lightweight -- The Calibration Book Plus Soundings and Ullages -- Drydocking and Stability -- Procedures and Calculations -- Ship Squat in Open Water and in Confined Channels -- Turning Circle Diameter (TCD) Values for Vessels in Shallow Waters -- Interaction Effects, Including Two Case Studies -- Rolling, Pitching, and Heaving Motions -- Synchronous Rolling and Parametric Rolling of Ships -- Effects of Change of Density on a Ship's Draft and Trim -- The Deadweight Scale -- The Trim and Stability Book -- Simplified Stability Information -- The Stability Pro-Forma -- Looking Forward into the Next Decade -- PART II: Endnotes -- Draft Surveys -- Quality Control -- Plus the Work of Ship Surveyors -- Extracts from the 1998 Merchant Shipping (Load Line) Regulations Number MSN 1752(M) -- Keeping Up to Date -- PART III: Appendices -- Appendix I: Summary of Stability Formulae -- Appendix II: SQA/MCA 2004 Syllabuses for Masters and Mates -- Appendix III: Specimen Exam Questions with Marking Scheme -- Appendix IV: 100 Revision One-Liners -- Appendix V: How to Pass Exams in Maritime Studies -- Appendix VI: Ship Stability Data Sheets -- Appendix VII: Capsize of the Herald of Free Enterprise -- A Journalistic Review -- References -- Answers to Exercises -- General Particulars of Selected Merchant Ships, Delivered 2007-2011 -- Nomenclature of Ship Terms.
Title from publisher's Web site; (ScienceDirect; viewed on Sept. 4, 2012).
Includes bibliographical references and index.
Keywords: Stability of ships; Stability of ships